A new concrete frost resistance evaluating method consider ing moisture content increase under outdoor exposure - Ma, Dequn; Senbu, Osamu; Kitagaki, Ryoma (Journal of Asian Concrete Federation, 2019)
Three kinds of concrete specimens were made and cured in water for two weeks. Then, half of the specimens were conducted with the accelerated freeze-thaw test and the critical degree of saturation test, directly. Besides, the other half were set in the actual outdoor environment for one year before con ducting the same tests. In the accelerated freeze-thaw test, there exists a critical mass moisture content which almost equals to the mass moisture content of the critical saturation Scr in the critical degree of saturation test. In addition, the cycle where the critical mass moisture content is reached is defined as the critical freeze-thaw cycle Nf. The effect of different outdoor exposure on concrete frost resistance can be evaluated by Nf. The outdoor exposure has a negative effect on concrete frost resistance.